Current Development of Virotherapy in Breast Cancer: A Brief Review - Sasmana I.; Putri P.; Dewi N.; Supadmanaba I.; Wihandani D. (Acta Medica Bulgarica)
Breast cancer is the cancer with the greatest incidence in the world by 2020. This cancer has a high mortality rate, has the capability of metastasizing, and causes damage to important organs of the human body. Therefore, a lot of studies have been done to find the best therapy to overcome this problem. However, cancer has various special abilities that make it survive and continue to invade its host body, for example, the ability to evade its host immune system by several mechanisms. One of the potential cancer therapies is virotherapy. Virotherapy is a therapeutic method using viruses to destroy cancer cells. Several mechanisms can be provided by viruses, such as stimulating the host immune system and inducing apoptosis of cancer cells. Especially for breast cancer, there are 4 groups of viruses based on their genome that have oncolytic capability, such as the dsDNA, dsRNA, + ssRNA, and -ssRNA groups. Currently, there are several therapeutic virotherapy-based modalities for breast cancer that are in clinical trial phases. Each trial has shown positive results in developing virotherapy for breast cancer.